2019
DOI: 10.1016/j.plabm.2019.e00147
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput test for diabetes care: An evaluation of the next generation Roche Cobas c 513 hemoglobin A1C assay

Abstract: ObjectivesThe level of glycated hemoglobin A (HbA1C) in blood is the preferred marker for diabetes monitoring and treatment. Here, we evaluate the analytical performance of the Roche Diagnostics Cobas c 513, a stand-alone HbA1C immunoassay analyzer.Design and MethodsPerformance was assessed with regards to imprecision, accuracy, linearity, method comparison against the Roche Cobas Integra 800 CTS, specimen stability, interference from common hemoglobin variants and hemoglobin F, and throughput.ResultsWithin-ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Interference by HbF is expected for immunoassay-based devices because HbA1c antibodies cannot recognize glycated HbF, whereas total Hb includes HbF, resulting in an artificially lowered HbA1c value [ 17 ]. Cobas c 513 was also expected to be affected by high HbF; a previous study reported a negative bias at HbF concentrations >10% with this device [ 18 ]. The actual percent bias in the present study was –9.8% ( Table 3 ), which was barely below the cut-off value of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Interference by HbF is expected for immunoassay-based devices because HbA1c antibodies cannot recognize glycated HbF, whereas total Hb includes HbF, resulting in an artificially lowered HbA1c value [ 17 ]. Cobas c 513 was also expected to be affected by high HbF; a previous study reported a negative bias at HbF concentrations >10% with this device [ 18 ]. The actual percent bias in the present study was –9.8% ( Table 3 ), which was barely below the cut-off value of 10%.…”
Section: Discussionmentioning
confidence: 99%